An updated ANGPTL3-4-8 model as a mechanism of triglyceride partitioning between fat and oxidative tissues. (January 2022) - Zhang, Ren; Zhang, Kezhong
Abstract: In mammals, triglyceride (TG), the main form of lipids for storing and providing energy, is stored in white adipose tissue (WAT) after food intake, while during fasting it is routed to oxidative tissues (heart and skeletal muscle) for energy production, a process referred to as TG partitioning. Lipoprotein lipase (LPL), a rate-limiting enzyme in this fundamental physiological process, hydrolyzes circulating TG to generate free fatty acids that are taken up by peripheral tissues. The postprandial activity of LPL declines in oxidative tissues but rises in WAT, directing TG to WAT; the reverse is true during fasting. However, the molecular mechanism in regulating tissue-specific LPL activity during the fed-fast cycle has not been completely understood. Research on angiopoietin-like (ANGPTL) proteins (A3, A4, and A8) has resulted in an ANGPTL3-4-8 model to explain the TG partitioning between WAT and oxidative tissues. Food intake induces A8 expression in the liver and WAT. Liver A8 activates A3 by forming the A3-8 complex, which is then secreted into the circulation. The A3-8 complex acts in an endocrine manner to inhibit LPL in oxidative tissues. WAT A8 forms the A4-8 complex, which acts locally to block A4's LPL-inhibiting activity. Therefore, the postprandial activity of LPL is low in oxidative tissues but high in WAT, directing circulating TG to WAT. Conversely, during fasting, reduced A8 expression in the liver and WAT disables A3 from inhibiting oxidative-tissue LPL and restores WAT A4's LPL-inhibiting activity, respectively. Thus, the fasting LPL activity is high in oxidative tissues but low in WAT, directing TG to the former. According to the model, we hypothesize that A8 antagonism has the potential to simultaneously reduce TG and increase HDL-cholesterol plasma levels. Future research on A3, A4, and A8 can hopefully provide more insights into human health, disease, and therapeutics.